Robot Responsibility and Moral Community - Gogoshin, Dane Leigh (Frontiers in Robotics and AI, 2021)
It is almost a foregone conclusion that robots cannot be morally responsible agents, both because they lack traditional features of moral agency like consciousness, intentionality, or empathy, and because of the apparent senselessness of holding them accountable. Moroever, although some theorists include them in the moral community as moral patients, on the Strawsonian picture of moral community as requiring moral responsibility, robots are typically excluded from membership. By looking closely at our actual moral responsibility practices, however, I determine that the agency reflected and cultivated by them is limited to the kind of moral agency of which some robots are capable, not the philosophically demanding sort behind the traditional view. Hence, moral rule-abiding robots (if feasible) can be sufficiently morally responsible and thus moral community members, despite certain deficits. Alternative accountability structures could address these deficits, which I argue ought to be in place for those existing moral community members who share these deficits.